ARCHITECTURE OF TRADITIONAL RESIDENTIAL BUILDINGS APPROPRIATE TO HISTORICAL CITIES - Usarov Jamoliddin Tolkinovich (Western European Studies, 2024)
The territory of Uzbekistan consists of regions with different climates, housing construction has a different composition in these regions and has a unique history of development. In the medieval centers of Bukhara, Khiva, Samarkand, Tashkent and Fargona valley, housing construction developed in different ways. In this, the influence of climatic conditions and religion on housing construction is extremely large
Keywords: Bukhara; Housing; Samarkand; climate